PENGARUH PERILAKU WAJIB PAJAK, PENGETAHUAN PAJAK DAN PENGGUNAAN E-FILLING, E-BILLING, E-FAKTUR TERHADAP KEPATUHAN WAJIB PAJAK - Ira Susanti; Afifudin Afifudin; Arista Fauzi Kartika Sari (Universitas Islam Malang, 2021)
This study aims to determine the effect of taxpayer behavior, tax knowledge, and the use of e-Filing, e-Billing, e-Faktur on taxpayer compliance at KPP Pratama South Malang. This research is a quantitative research using primary data. The population in this study were all individual taxpayers registered at KPP Pratama South Malang. The sample size in this study was determined using the slovin method which resulted in 99 respondents. The sampling method used in this study is convenience sampling. Data collection in this study was carried out by distributing questionnaires to individual taxpayers at KPP Pratama South Malang. The analytical technique used in this research is multiple linear regression with the help of SPSS program. Based on the partial test results, it can be seen that the use of e-Billing, e-Faktur has a positive and significant effect on individual taxpayer compliance. while the behavior of taxpayers, tax knowledge, the use of e-Filling has no effect on individual taxpayer compliance.Keywords: Taxpayer behavior, Tax knowledge, use e-Filing, e-Billing, e-Faktur, Tax compliance